Optimal Capacity Adjustment by a Multiplant Firm - Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 1999)
The paper studies the effect of scale economies on the optimal capacity adjustment of a mutiplant firm. It is shown that with increasing economies of scale plants are ranked in decreasing order, after which the optimal choice is to scrap the largest one. On the contrary, if there are decreasing economies of scale the optimal policy would be to wait before abandoning intermediate plants. That is, decreasing economies of scale amplify the effect of uncertainty on disinvestment and tend to increase the plant's life.
Keywords: D92; L11; 330; Exit; Option value; Irreversibility